First record of the alien exotic sap beetle Phenolia (Lasiodites) picta (Coleoptera: Nitidulidae) in Greece - Kalaentzis, Konstantinos; Mpamnaras, Athanasios; Kazilas, Christos (ENTOMOLOGIA HELLENICA, 2019)
The exotic sap beetle Phenolia (Lasiodites) picta (Macleay, 1825) is recorded for the first time in Greece. In August 2018, a nitidulid beetle was found near Mt. Pelion of Central Greece. It was later identified as P. picta, a recent alien species in Europe, previously recorded from Spain, France, and Turkey. Photographic material and information on the species’ distribution, biology, and potential economic and ecological implications are presented and discussed.